The Time of My Life - Swayze, Patrick and Niemi, Lisa (London Simon & Schuster, 2009)
A timely and heartfelt memoir from movie legend Patrick Swayze and wife Lisa Niemi, completed just weeks before Swayze's death
Include Illustration
Keywords: Swayze, Patrick -- Motion picture actors and actresses -- United States